1998
DOI: 10.1111/j.1745-4522.1998.tb00122.x
|View full text |Cite
|
Sign up to set email alerts
|

OXIDATIVE STABILITY OF FROZEN LIGHT AND DARK MUSCLES OF SAITHE (POLLACHIUS VIRENS L.)

Abstract: Saithe, a lean gadoid fish, was processed and stored at −10C, −20C and −30C as normal skinless fillets and as deep‐skinned fillets. Properties related to lipid oxidation in the dark and light muscle tissues and in the two types of fillets were investigated after 6 to 9 months of storage. The lipid content and fatty acid profiles indicated the presence of relatively large amounts of triacylglycerols in the dark muscle. Prolonged storage at −10C and −20C resulted in a decrease in the content of n‐3 polyunsaturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…After 2 or more months of frozen storage, samples stored at −30 • C had significantly higher levels of TBARS (p < 0.001 for all) than samples stored at lower temperatures. There was no difference between TBARS levels for samples stored at −40 to −80 • C. Similar results for saithe were reported by Dulavik et al (1998), andAubourg et al (2004) observed higher peroxide value (PV) and TBARS content in horse mackerel fillets stored at −20 compared to −80 • C. Rodríguez et al (2007) only observed a low degree of lipid oxidation (PV, TBARS) in farmed coho salmon stored at −20 • C and did not observe any significant increase in TBARS content until after 15 months of frozen storage (TBARS-value 0.54 mg/kg). This value corresponds approximately to the level of 8.3 µmol/kg sample for trout stored at −20 • C for 8 months in our experiment.…”
Section: Tbarssupporting
confidence: 91%
“…After 2 or more months of frozen storage, samples stored at −30 • C had significantly higher levels of TBARS (p < 0.001 for all) than samples stored at lower temperatures. There was no difference between TBARS levels for samples stored at −40 to −80 • C. Similar results for saithe were reported by Dulavik et al (1998), andAubourg et al (2004) observed higher peroxide value (PV) and TBARS content in horse mackerel fillets stored at −20 compared to −80 • C. Rodríguez et al (2007) only observed a low degree of lipid oxidation (PV, TBARS) in farmed coho salmon stored at −20 • C and did not observe any significant increase in TBARS content until after 15 months of frozen storage (TBARS-value 0.54 mg/kg). This value corresponds approximately to the level of 8.3 µmol/kg sample for trout stored at −20 • C for 8 months in our experiment.…”
Section: Tbarssupporting
confidence: 91%
“…Lipid oxidation was estimated by determining the amount of 2-thiobarbituric acid reactive substances (TBARS) in an aqueous trichloroacetic acid extract (Witte et al 1970) as described previously (Dulavik et al 1998). Two replicate extractions were made for each pooled sample of muscle cubes.…”
Section: Analysesmentioning
confidence: 99%
“…In general, one would expect a steady increase in MDA over the storage time as it has been seen by several authors, for example in saithe ( Pollachius virens L .) during 9 months of storage at −10 and −20 °C (Dulavik, SÿRensen, Barstad, Horvli, & Olsen, ), in Wallago attu fish during 30 days of storage at −12 °C (Gupta, Gandotra, Koul, Gupta, & Parihar, ) and in Spanish mackerel ( Scomberomorus commersoni ) during 6 months storage at −18 °C (Nazemroaya, Sahari, & Rezaei, ). Additionally, Jezek and Buchtova () reported a significant increase in the amount of MDA and PV value during 11 days of storage in the normal package of common carp ( C. carpio L .)…”
Section: Discussionmentioning
confidence: 99%